Serotype and genotype diversity of dengue viruses circulating in India: a multi-centre retrospective study involving the Virus Research Diagnostic Laboratory Network in 2018. (October 2021) - Alagarasu, K.; Patil, J.A.; Kakade, M.B.; More, A.M.; Yogesh, B.; Newase, P.; Jadhav, S.M.; Parashar, D.; Kaur, H.; Gupta, N.; Vijay, N.; Narayan, J.; et al.
Highlights: Dengue virus serotypes were tested in 4963 samples collected across India in 2018. DENV-2 was the most prevalent serotype in many states of India. Two genotypes of DENV-1 (I and V) were circulating. Two lineages of DENV-2 genotype IV were circulating. DENV-3 genotype III and DENV-4 genotype-I were circulating. ABSTRACT: Objectives: A retrospective study was undertaken to investigate the circulating dengue virus (DENV) serotypes and genotypes in India in 2018. Methods: In total, 4963 samples referred to virus research diagnostic laboratories (n=21), the Indian Council of Medical Research-National Institute of Virology (ICMR-NIV) and ICMR-NIV field units ( n =2) for diagnosis of dengue in 2018 were tested using a real-time reverse transcription polymerase chain reaction assay for the presence of DENV serotypes. Representative samples were sequenced for the envelope (E) gene. Results: Regional diversity was observed with regard to the dominant circulating serotypes. DENV-2 was found to be the most common serotype in many states. Thrombocytopenia, petechiae and malaise were associated with DENV-2 infection. Phylogenetic analyses of DENV E gene sequences revealed the circulation of genotypes I and V of DENV-1, two lineages of DENV-2 genotype IV, DENV-3 genotype III and DENV-4 genotype I. Conclusions: This study found regional differences in the prevalence of circulating DENV serotypes in India, and provides baseline data for continuous molecular surveillance. Molecular surveillance may have implications for predicting large-scale outbreaks of dengue if regional shifts in the predominantly circulating serotypes and genotypes are detected during the early phase of the dengue season.